Influence of surface on impact shock experienced during a fencing lunge - Greenhalgh, A.; Bottoms, L.; Sinclair, J. (Journal of Applied Biomechanics, 2013)
The purpose of this study was to investigate the effect of sports surface on the magnitude of impact shock experienced during a lunge movement. Thirteen experienced, competitive fencers (age 32.4 ± 4.6 years; height 178.4 ± 7.2 cm; mass 74.4 ± 9.1 kg) performed 10 lunges on four different surfaces: concrete with an overlaid vinyl layer (COVL), wooden sprung court surface (WSCS), metallic carpet fencing piste overlaid on the WSCS, and aluminum fencing piste overlaid on the WSCS. An accelerometer measured accelerations along the longitudinal axis of the tibia at 1000 Hz. The results identified a significantly (P < .05) larger impact shock magnitude was experienced during a lunge on the COVL (14.88 ± 8.45 g) compared with the WSCS (11.61 ± 7.30 g), WSCS with metallic carpet piste (11.14 ± 6.38 g) and WSCS with aluminum piste (11.95 ± 7.21 g). Furthermore, the two types of piste used had no significant effect the impact shock magnitude measured when overlaid on the WSCS compared with the WSCS on its own. The results of this investigation suggest that occurrences of injuries related to increased levels of impact shock may be reduced through the utilization of a WSCS as opposed to a COVL surface during fencing participation.